Numerical Simulation of a Horizontal Well With Multi-Stage Oval Hydraulic Fractures in Tight Oil Reservoir Based on an Embedded Discrete Fracture Model - Yang, Zhi-dong; Wang, Yong; Zhang, Xu-yang; Qin, Ming; Su, Shao-wen; Yao, Zhen-hua; Liu, Lingfu (Frontiers in Energy Research, 2020)
Tight oil is a kind of unconventional oil and gas resource with great development potential. Due to the unconventional characteristics of low porosity and low permeability in tight oil reservoirs, single wells generally have no natural productivity, and industrial development is usually conducted in combination with horizontal wells and hydraulic fracturing techniques. To capture the flow behavior affected by fractures with complex geometry and interaction, we adopted embedded discrete fracture models (EDFMs) to simulate the development of fractured reservoirs. Compared with the traditional discrete fracture models (DFMs), the embedded discrete fracture models (EDFMs) can not only accurately represent the fracture geometry but also do not generate a large number of refine grids around fractures and intersections of fractures, which shows the high computational efficiency. To be more consistent with the real characteristic of the reservoir and reflect the advantage of EDFMs on modeling complex fractures, in this work, the hydraulic fractures are set as oval shape, and we adopted 3-dimensional oil–gas two-phase model considering capillary forces and gravity effects. We developed an EDFM simulator, which is verified by using the fine grid method (FGM). Finally, we simulated and studied the development of tight oil without and with random natural fractures (NFs). In our simulation, the pressure varies widely from the beginning to the end of the development. In real situation, tight oil reservoirs have high initial pressure and adopt step-down bottom hole pressure development strategy where the bottom hole pressure of the last stage is below the bubble point pressure and the free gas appears in the reservoir. Modeling studies indicate that the geometry of fracture has a great influence on the pressure and saturation profiles in the area near the fractures, and dissolved gas flooding contributes to the development of tight oil, and NFs can significantly improve production, while the effect of the stress sensitivity coefficient of NFs on production is more significant in the later stage of production with lower reservoir pressure.